1979
DOI: 10.1093/clinchem/25.7.1317
|View full text |Cite
|
Sign up to set email alerts
|

New micro-turbidimetric method for determination of protein in cerebrospinal fluid and urine.

Abstract: We report a new micro-scale (0.1-mL sample) turbidimetric method for determination of protein by use of benzethonium chloride in alkali. The method is highly specific for protein, has a higher sensitivity than the classic method of Lowry et al., and shows satisfactory reproducibility and recovery. The turbidity produced in our method is the same for albumin and gamma-globulin and is more stable than in Meulemans' method (in which sulfosalicylic acid is used) or in the method of Bossak et al. (in which trichlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…In clinical laboratories, turbidimetric methods such as the benzethonium chloride method (12), and dyebinding methods utilizing pigments such as CBB and PRM (2,3) are commonly used for measurement of urinary total protein. Because pigment methods have a higher sensitivity than turbidimetric methods (13), and the AV6B method is a pigment method, we compared the AV6B method with two other pigment methods, the CBB and PRM methods.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical laboratories, turbidimetric methods such as the benzethonium chloride method (12), and dyebinding methods utilizing pigments such as CBB and PRM (2,3) are commonly used for measurement of urinary total protein. Because pigment methods have a higher sensitivity than turbidimetric methods (13), and the AV6B method is a pigment method, we compared the AV6B method with two other pigment methods, the CBB and PRM methods.…”
Section: Discussionmentioning
confidence: 99%
“…* and in a limited 3-week study in mice and rats by Suurmeijer et u I .~ However, except for the monitoring of circulating serum iron level^,^ no metabolic investigations were performed in these studies and no examination was made of the possibility of endo- Several investigators have demonstrated that a high blood level of tracer is required to saturate the systemic mononuclear phagocytic system before significant uptake by the mesangium is observed. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]22 The large intravenous dose of Imposil required to produce significant mesangial uptake in this study produced a toxic reaction which may have been associated with a redistribution of renal blood flow, resulting in disappearance of tracer from some glomerular capillaries whilst it was still visible in vasa rectae (Fig. I).…”
Section: Discussionmentioning
confidence: 99%
“…Within 30 minutes of adding blood to the urine samples, the urine protein and creatinine concentrations were assessed using a benzethonium chloride assay (Urine/CSF protein method, Roche Diagnostics) (Iwata and Nishikaze 1979;Luxton et al 1989), and the Jaffe method (Creatinine Method, Roche Diagnostics) ( Bartels et al 1972), respectively.…”
Section: Methodsmentioning
confidence: 99%